Analisis Manajemen Risiko pada UMKM “Tahu Walek Ponkq” Jember - Dian Septi; Amelia Putri Maharani; Abu Bakar Abdul Rachman Bazed; Arya Abim Abdillah; Nurul Qomariah; Nursaid Nursaid (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Every business that is undertaken must have competition to increase business. Small, medium enterprises or commonly called SMEs are businesses that are easy to run for everyone who wants to do business. Competition will always exist in every area of life, including MSME businesses. Every business that is run must have competition and challenges that must be faced. To face competition and challenges in the business world, every MSME must innovate products and services, as well as develop human and technological resources. Every business that is carried out must contain risks. Therefore, as MSMEs, it is also necessary to know what risk management is. Risk management is needed to anticipate or reduce the possibility of risk occurring in a business. This paper aims to describe the risks faced by UMKM Tahu Walek